Respuesta :

x+9=18+(-2x)
x+9=18-2x | add 2x to the equation and you get
3x+9=18    | substract 9
3x=9          | divide by 3
x=3
x + 9 = 18 + -2x

First, simplify 18 + -2x to 18 - 2x / Your problem should look like: x + 9 = 18 - 2x
Second, subtract 9 from both sides. / Your problem should look like: x = 18 - 2x - 9
Third, simplify 18 - 2x - 9 to -2x + 9 / Your problem should look like: x = -2x + 9
Fourth, add 2x to both sides. / Your problem should look like: x + 2x = 9
Fifth, simplify x + 2x to 3x. / Your problem should look like: 3x = 9
Sixth, divide both sides by 3. / Your problem should look like: x = [tex] \frac{9}{3} [/tex]
Seventh, simplify [tex] \frac{9}{3} [/tex] to 3. / Your problem should look like: x = 3

Answer: x = 3